Proceso de inmatriculación de la zona de protección y conservación ecológica humedal del Alto Mayo - Pinchi Guerra, Greta (2014)
Within the process of decentralization, by Supreme Decree N° 038-2004-PCM, adopted the "Annual Plan for Transfer of sectorial expertise to local and regional governments of the year 2004"which corresponded to the specific functions that allow the exercise of exclusive competences stated in articles 35 or of the Law on foundations of Decentralization and in article 10° of the Regional Governments Organic Law. On the nationai Ievel, the governing organ for the unmatriculation is the National Superintendence of State Goods - SBN, whose mission is " to regulate the administration and control of the State goods, developing mechanisms that allow the efficient management of the same ones, in order to maximize its economic and social performance, inside the policies that for these ends the national government establishes. The San Martín department, was one of the frrst to have the transfer of competencies linked to the administration of state property, Ministerial Resolution No. 656-2006-EF- 1 O; understanding the importance of this function in the year 2007, when the San Martin Regional Government, through the Territorial Administration Sub management - SGTA. Between 2008 and 201 O the Regional Government of St Martín across the SGAT has come realizing the unmatriculation of spaces established as Areas of Municipal Conservation and that possess Municipal Ordinances; under the tenets of be spaces with high environmental value and which require shelter at the request of the Local Government, because of this insecurity in the Peruvian legal framework. On 24 December 2010, through Regional Ordinance 037-2010-, CO-OTERATION/CR approving the new Regulation on the Organization of functions of the San Martín Regional Government, creating regional environment authority - ARA, that absorbs the Sub Management ofTerritorial Administration, to the same as it is- diligently- develop a directive to establish procedures for the registration and administration of estates under the surface areas of protection and ecological conservation belonging to the S tate - San Martín Regional Government; that do not possess a figure of already established conservation and that already recount with procedures registries in the legal Peruvian frame. This document seeks to be the basis for the preparation of the directive, the same that set the tone for determine which spaces, belonging to the areas of protection and ecological conservation, are liable to be registered under the legal framework of the National System of State Property and those that will have to be kept free to be inscribed under other modalities of grant of rights regulated by national laws. The indicated last thing is a responsibility ofthe Environmental Regional Authority.